El docente y la innovación curricular - Bautista Orbe, Jenny Rocio (2018)
Curricular innovation and professor are two broad fields of study in education, however, in this research was specifically analyzed the problems faced in Cotopaxi province, in Pujilí, Angamarca neighborhood, at "Chone” Educational Institution belonging to zone 3 district 05D04, the problem is centered on how to combine this theoretical proposal with the current rural scholastic situation, especially in the fulfillment of the teacher contents domain with each area of study. The research objectives established the scientific basis for teaching and curricular innovation in order to improve the relationship between learning standards. The methodology applied in this research is descriptive with a quantitative approach and the instrument was a questionnaire with closed-ended questions, in which data collected through surveys and interviews to get teaching overview work and conduct a thorough data analysis. The teacher considered as an independent variable: the teaching work, the professionalism, its ability as a mediator, the quality standards, while the dependent variable was analyzed the teaching and learning processes, the curriculum structure and content, the didactic methods, the evaluation criteria, teamwork and interaction in the classroom. This is a research oriented to education and to have as beneficiaries to the school institution, it can be established that this research has a socio-educational contribution to determine how the educational curriculum is integrated into the teaching innovation and the current Ecuadorian educational system. This research becomes a technical resource, because it can be applied to different institutions. This research was feasible because the institution opened the doors to make known how academic activities are developed, from the perspective of one's own needs. This research was possible because it had information obtained in the process and in the study period. Finally, this research was necessary because the current analysis of curricular innovation in Ecuador is an issue that must be addressed and emphasized in a timely manner.